Derivatives of the beta-Crinane Amaryllidaceae Alkaloid Haemanthamine as Multi-Target Directed Ligands for Alzheimer's Disease - Kohelova, Eliska; Perinova, Rozalie; Maafi, Negar; Korabecny, Jan; Hulcova, Daniela; Marikova, Jana; Kucera, Tomas; Martinez Gonzalez, Loreto; Hrabinova, Martina; Svrčková, Katarína; Novakova, Lucie; De Simone, Angela; et al. (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
Twelve derivatives 1a-1m of the beta-crinane-type alkaloid haemanthamine were developed. All the semisynthetic derivatives were studied for their inhibitory potential against both acetylcholinesterase and butyrylcholinesterase. In addition, glycogen synthase kinase 3 beta (GSK-3 beta) inhibition potency was evaluated in the active derivatives. In order to reveal the availability of the drugs to the CNS, we elucidated the potential of selected derivatives to penetrate through the blood-brain barrier (BBB). Two compounds, namely 11-O-(2-methylbenzoyl)-haemanthamine (1j) and 11-O-(4-nitrobenzoyl)-haemanthamine (1m), revealed the most intriguing profile, both being acetylcholinesterase (hAChE) inhibitors on a micromolar scale, with GSK-3 beta inhibition properties, and predicted permeation through the BBB. In vitro data were further corroborated by detailed inspection of the compounds' plausible binding modes in the active sites of hAChE and hBuChE, which led us to provide the structural determinants responsible for the activity towards these enzymes.
Deriváty beta-Crinane Amaryllidaceae Alkaloid Haemanthamine jako vícecílové cílené ligandy pro Alzheimerovu chorobu
Keywords: haemanthamine; Amaryllidaceae; Alzheimer's disease; acetylcholinesterase; butyrylcholinesterase; glycogen synthase kinase-3 beta inhibition; docking studies; haemanthamin; Amaryllidaceae; Alzheimerova choroba; acetylcholinesteráza; butyrylcholinesteráza; inhibice glykogen syntázy kinázy-3 beta; dokovací studie